Skopos Theory and Cultural Preservation in the Short Film Tilik (2018) - Paramita, Niken; Sampurna, Riza Adi (Journal of Language Intelligence and Culture, 2025)
This study explores how Javanese cultural values are translated into English subtitles in the short film Tilik (2018). Javanese communication relies on speech levels that mark hierarchy and on politeness strategies that avoid conflict, both of which are challenging to render in English. Using a qualitative case study of 427 subtitle lines, the data were transcribed, annotated, and analyzed to identify translation strategies. The findings show that clarity and accessibility were prioritized for global viewers: speech levels were simplified into polite forms, and indirect expressions were made more direct. At the same time, some culture-specific terms were preserved, and pauses or hesitations were represented with punctuation to mimic interactional style. These results suggest that subtitling is not merely linguistic transfer but cultural negotiation, balancing fidelity to local identity with international readability. The study highlights the importance of socio-cultural awareness in subtitler training and contributes to research on subtitling in marginalized languages.